Community participation through cooperatives in addressing basic services the Philippine experience - Teodosio, Virginia Alon (Philippine Journal of Labor and Industrial Relations, 2010)
The purpose of this paper is to examine the role of cooperatives in helping the poor to access services at the community level. In the formation of strong cooperatives, there are critical cultural factors that predicate key relationships between social capital, the building of a critical mass and the role of women.